Method for preparing iron-silicon-copper alloy phase change energy storage capsule by using organic silicon waste contact

The preparation of ferrosilicon copper alloy energy storage capsules through ball-floor alloy technology and spray method has solved the problem of insufficient recycling and utilization of industrial silicone waste contacts and silicon slag resources and poor sealing of high-temperature energy storage materials, and achieved efficient resource recycling and high-quality resource recovery Preparation of performance energy storage materials, suitable for high-temperature energy storage field.

CN119119964APending Publication Date: 2024-12-13KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411210297.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the resource recycling and utilization of industrial silicone waste contacts and industrial silicon slag is insufficient, resulting in environmental pollution and resource waste. At the same time, the high-temperature smelting alloying process has problems of high energy consumption and component segregation. Traditional energy storage materials are Poor sealing and easy oxidation under high temperature conditions.

Method used

Using ball-mill alloying technology to roast the silicone waste contacts under an argon atmosphere, mix iron and copper powder, combine oxides as capsule shells for industrial silicon slag, and prepare ferrosilicon copper alloy energy storage capsules through high-energy ball milling and spraying to avoid High-temperature alloying segregation and oxidation realize the coordinated recovery of silicon and copper resources.

Benefits of technology

Improve the phase transition temperature and energy storage density of energy storage materials, ensure durability and safety in high temperature environments, reduce copper usage, improve the operating efficiency and service life of the system, and solve the problems of waste of resources and high costs. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119964A_ABST
    Figure CN119119964A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of resource circulation and energy storage, in particular to a method for preparing an iron-silicon-copper alloy phase change energy storage capsule by utilizing organic silicon waste contact bodies, which comprises the following steps: S1, roasting the waste contact bodies in an argon atmosphere to remove organic matters in the waste contact bodies; s2, mixing with iron powder and copper powder; s3, alloying treatment is carried out; s4, performing grinding treatment and screening to obtain silicon slag powder; s5, uniformly mixing with a certain amount of MgO and Al2O3 powder and a caking agent, adding water, and stirring to pulpify the powder; s6, injecting into a mold, pressing to obtain a capsule main body and a capsule cover, and pre-sintering after demolding; s7, the alloy powder is packaged in a capsule shell, and a gap between the capsule shell and a capsule cover is filled with the slurry in the step S5; s8, performing high-temperature sintering and sealing treatment on the capsule; synergistic recycling of silicon and copper resources and industrial silicon slag in the waste contact body is achieved, and the energy storage capsule prepared through the technology has the high phase change temperature and energy storage density and can be widely applied to the field of high-temperature energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource recycling and energy storage, and in particular to a method for preparing an iron-silicon-copper alloy phase-change energy storage capsule by utilizing waste organic silicon contacts. Background Art

[0002] Organosilicon materials are widely used in aerospace, medical and health, and new energy industries due to their excellent performance in many aspects. Organosilicon monomers are important raw materials for the synthesis of organosilicon materials. The most widely used monomer is dimethylchlorosilane (M2). At present, the industrial production of M2 mainly adopts the "direct synthesis method". In the direct synthesis process, in order to maintain stable production, some unreacted silicon powder and inactivated catalysts must be discharged from the reactor to form industrial waste slag, which is called organosilicon waste contacts. Waste contacts are classified as waste organic solvents and wastes containing organic solvents in the National List of Hazardous Wastes (2021). Improper treatment can easily cause serious environmental pollution. In addition, waste contacts contain 65-75% silicon and 10-15% copper. If the silicon and copper resources can be effectively recovered, it will produce considerable resource benefits and economic benefits. However, the existing mainstream process only extracts copper from waste contacts by acid leaching, and the copper-silicon slag is often buried or incinerated, resulting in a large loss of high-quality silicon resources.

[0003] Since the silicon melt obtained by smelting in an electric arc furnace still contains a large amount of impurities, the subsequent application of industrial silicon products is severely limited. In order to improve the purity of industrial silicon and meet its application needs in high-end fields, it is often necessary to refine the silicon melt obtained by smelting in an electric arc furnace outside the furnace. The main methods of refining outside the furnace are slag refining and air blowing refining, both of which are to improve the purity of industrial silicon by converting impurities in the melt into oxides and entering the slag phase, and transferring them out of the refining container by slag cleaning. The refining process will produce a large amount of industrial silicon slag, the main components of which are metal oxides such as silicon oxide, silicate, aluminum oxide and calcium oxide, as well as a small amount of mixed silicon. Due to the complex composition of silicon slag, it is difficult to purify and recover the valuable metals in it. Using it to prepare the packaging shell of phase change energy storage materials can provide a new way to recycle silicon slag.

[0004] As human beings' demand for energy and green requirements continue to increase, the proportion of green energy such as solar energy and wind energy in today's energy supply is also increasing, but the exploitation and utilization of such energy is often unstable, so advanced energy storage technology is needed to regulate it. Compared with traditional molten salt thermal storage, alloy phase change energy storage materials have higher heat release temperature and energy storage density, lower volume expansion coefficient and other advantages, and are expected to be widely used in the field of high-temperature energy storage. Silicon copper alloy has excellent thermal properties due to the high thermal conductivity of copper and the strong heat storage performance of silicon, but due to the large consumption of copper, the use of silicon copper alloy does not have cost advantages. The iron-silicon-copper ternary alloy prepared by introducing a certain amount of iron on the basis of the original silicon-copper alloy can reduce the amount of copper while ensuring the thermal properties of the alloy, and improve the product cost performance. In general, iron-silicon-copper alloy has considerable application prospects in the field of heat storage.

[0005] The existing Chinese patent document CN202010003167.9 discloses a metal microcapsule with a metal oxide as a shell layer and its preparation method and application. The metal microcapsule has a core-shell structure, including a core and a shell layer wrapped outside the core; the core is a single metal powder or alloy powder, and the shell layer is a metal oxide shell layer corresponding to the single metal in the core or the metal in the alloy, and the phase change energy storage microcapsule is prepared by controlling the temperature and heating and calcining in an oxygen atmosphere in one step; the existing Chinese patent document CN201710129236.9 discloses a metal and alloy phase change energy storage microcapsule and its preparation method, which has a core-shell structure, including a core and a shell layer; the core is a metal alloy or metal powder, and the shell layer is divided into an inorganic shell layer and a metal compound shell layer; the inorganic shell layer is one or more inorganic substances; the metal compound shell layer is a metal nitride or a metal oxide shell layer, and the phase change energy storage microcapsule is prepared by a sol-gel method. Existing alloy preparation methods often use high-temperature smelting, which is often accompanied by problems such as excessive energy consumption and component segregation. The high-energy ball milling method can achieve the purpose of preparing alloys at a lower temperature, and the prepared alloy exists in the form of powder with uniform composition. At present, the encapsulation of metal energy storage capsules often cannot miss the sacrifice of surface metal to transform it into a stable oxide, thereby isolating the inner metal from the external environment to achieve the purpose of encapsulation. However, this method is only applicable to the encapsulation of metal particles at the micron level and below, and is difficult to use in the encapsulation of large-sized capsules. At the same time, the oxidation of the surface metal also causes the loss of phase change materials, which is not conducive to the improvement of the heat storage capacity of the capsule. Large-sized capsules encapsulated with stable materials often mean a larger core-shell ratio, which can store more energy per unit volume. The combination of ball milling alloying and macro-encapsulation technology to prepare large-sized heat storage capsules is an effective strategy to improve energy efficiency. The use of organic silicon waste contacts and industrial silicon slag as raw materials to prepare alloy heat storage capsules is also of great significance to sustainable development. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an iron-silicon-copper alloy energy storage capsule using waste contacts and industrial silicon slag, which adopts ball milling alloying to avoid the segregation phenomenon and high energy consumption problems in the high-temperature alloying process, and adopts industrial silicon slag with oxide as the main component to prepare the capsule shell, which effectively avoids the leakage and oxidation of the alloy, and at the same time realizes the coordinated recovery and reuse of silicon-copper resources in waste contacts and industrial silicon slag. The energy storage capsule prepared by this process has a high phase transition temperature and energy storage density, and can be widely used in the field of high-temperature energy storage.

[0007] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0008] A method for preparing a silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts comprises the following steps:

[0009] S1, calcining the waste organosilicon contact body in an argon atmosphere to remove organic matter therein;

[0010] S2, mixing the waste silicone contact body treated in S1 with a certain proportion of pure iron powder and pure copper powder;

[0011] S3, alloying the mixed material in S2 using a high energy ball mill;

[0012] S4, grinding the industrial silicon slag and sieving to obtain silicon slag powder with a target particle size;

[0013] S5, the silicon slag powder obtained from S4 and a certain amount of MgO and Al 2 O 3 The powder and sodium carboxymethyl cellulose binder are mixed evenly, and then a certain amount of water is added to the mixture by spraying and stirring continuously to make the powder slurry;

[0014] S6, injecting the slurry obtained in S5 into a cylindrical mold, pressing to obtain a matching capsule body and capsule cover, and pre-sintering after demoulding;

[0015] S7, encapsulating the alloy powder obtained in S3 into the capsule shell obtained in S6, and filling the gap between the capsule shell and the capsule cover with the slurry in S5;

[0016] S8, subjecting the capsule obtained in S7 to high temperature sintering and sealing treatment.

[0017] Furthermore, in said S1, the calcination temperature is 300-900° C., and the calcination time is 30-300 min.

[0018] Furthermore, the amount of iron powder added in S2 is 0.5 to 2 times the mass of the waste contact body, and the amount of copper powder added is 1 to 5 times the mass of the waste contact body;

[0019] Furthermore, the high-energy ball mill in S3 is subjected to vacuum treatment, and the parameters of the ball mill are set to a speed of 350-600 r / min, forward rotation of 10-30 min / time, pause of 5 min, reverse rotation of 10-30 min / time, and a total ball milling treatment time of 15-30 h;

[0020] Furthermore, the particle size of the silicon slag powder in S4 is required to be less than 100 μm;

[0021] Furthermore, the amount of MgO added in S5 is 1-10% of the mass of silicon slag powder, and Al 2 O 3 The addition amount is 5-20% of the mass of silicon slag powder, and the addition amount of binder is silicon slag powder, MgO and Al 2 O 3 1-5% of the mass;

[0022] Furthermore, the capsule shell in S6 has an inner diameter of 10 to 500 mm, an inner height of 10 to 1000 mm, and a thickness of 2 to 5 mm, an inner diameter of the capsule cover is 2 to 5 mm larger than the outer diameter of the shell, an inner height is consistent with the outer height of the shell, and a thickness of 1 to 5 mm;

[0023] Furthermore, the pre-sintering temperature in S6 is 300° C., the heating rate is 3° C. / min, the temperature is kept at 300° C. for 60 to 150 min, and the temperature is naturally lowered.

[0024] Furthermore, the sintering temperature in S8 is 1100-1500° C., the temperature is kept for 100-200 min, and the heating and cooling rate is 5° C. / min.

[0025] Beneficial effects of the present invention:

[0026] In terms of resource recovery, the present invention uses high-temperature roasting technology to efficiently remove organic matter from waste organic silicon contacts, simplifies the waste treatment process, and provides high-quality raw materials for further utilization. 2 O 3 The oxides are finely mixed to form a high-temperature resistant and high-strength composite material, which provides a reliable material for the packaging of alloy materials while realizing the recycling of silicon slag resources.

[0027] The present invention realizes mechanical alloying of the ternary system of iron, silicon and copper by introducing high-energy ball milling technology during the alloying process. Mechanical force is used to refine and evenly mix the materials to form a nano-scale particle structure. The advantage of high-energy ball milling is that it can break the crystal structure barriers of the material at room temperature, promote solid-state diffusion between different elements, and form a homogeneous alloy structure. The introduction of iron further improves the hardness and wear resistance of the alloy, while reducing the dependence on copper, thereby reducing the preparation cost. Such an alloying process not only improves the thermal conductivity and mechanical stability of the alloy, but also enhances the corrosion resistance of the material, fundamentally solving the problems of uneven performance and high cost in traditional processes.

[0028] In the preparation of the energy storage capsule, the present invention further ensures the integrity and stability of the capsule by optimizing the capsule structure and combining high-temperature sintering, preventing possible oxidation and material loss during the high-temperature phase change process, thereby ensuring the durability and safety of the energy storage alloy in a high-temperature environment. This effectively solves the problem of poor sealing and easy oxidation of traditional energy storage materials under high-temperature conditions.

[0029] Ultimately, the present invention significantly improves the overall performance and safety of energy storage materials. In high-temperature energy storage applications, the optimized capsule structure can not only effectively encapsulate and stabilize the alloy powder, but also maintain a long-term stable phase change temperature and high energy storage density under thermal cycling conditions. As a result, the present invention provides an innovative and economical technical route for the field of high-temperature energy storage, significantly improves the operating efficiency and service life of the system, and promotes the development and application of energy storage technology.

[0030] Through the above-mentioned systematic technical improvements and process innovations, the present invention successfully solves the problems existing in traditional technologies such as resource waste, alloy instability, high cost and insufficient safety of energy storage materials, and opens up a new path for waste resource utilization and preparation of high-performance energy storage materials.

[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0033] Figure 1 is a process flow chart of the present invention;

[0034] Figure 2 It is a schematic diagram of the structure of the iron-silicon-copper alloy energy storage capsule of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The chemical composition of the waste silicone contacts treated in the following examples is: 65.33% silicon, 12.32% copper, 4.64% iron, 0.23% aluminum, 0.35% calcium, 0.98% zinc, 2.32% carbon, and 13.13% others; the chemical composition of industrial silicon slag is: 29.41% silicon, 0.45% iron, 7.82% aluminum, 15.11% calcium, 2.53% carbon, 43.31% oxygen, and 1.37% others.

[0037] Example 1

[0038] As described in this embodiment, a method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts has the following specific steps:

[0039] S1, calcining the waste contactor in an argon atmosphere to remove organic matter therein;

[0040] S2, mixing the waste contact body processed in S1 with a certain proportion of pure iron powder and pure copper powder;

[0041] S3, alloying the mixed material in S2 using a high energy ball mill;

[0042] S4, grinding the industrial silicon slag and sieving to obtain silicon slag powder with a target particle size;

[0043] S5, the silicon slag powder obtained from S4 and a certain amount of MgO and Al 2 O 3 The powder and sodium carboxymethyl cellulose binder are mixed evenly, and then a certain amount of water is added to the mixture by spraying and stirring continuously to make the powder slurry;

[0044] S6, injecting the slurry obtained in S5 into a cylindrical mold, pressing to obtain a matching capsule body and capsule cover, and pre-sintering after demoulding;

[0045] S7, encapsulating the alloy powder obtained in S3 into the capsule shell obtained in S6, and filling the gap between the capsule shell and the capsule cover with the slurry in S5;

[0046] S8, subjecting the capsule obtained in S7 to high temperature sintering and sealing treatment.

[0047] In this embodiment, the calcination temperature in S1 is 300° C. and the calcination time is 30 min.

[0048] In this embodiment, the amount of iron powder added in S2 is 0.5 times the mass of the waste contact body, and the amount of copper powder added is 1 times the mass of the waste contact body;

[0049] In this embodiment, the high-energy ball mill described in S3 is vacuumized, and the ball mill parameters are set to a speed of 350 r / min, forward rotation for 10 min / time, pause for 5 min, reverse rotation for 10 min / time, and a total ball milling time of 15 h;

[0050] In this embodiment, the particle size of the silicon slag powder described in S4 is required to be less than 100 μm;

[0051] In this embodiment, the amount of MgO added in S5 is 1% of the mass of silicon slag powder, and Al 2 O 3 The addition amount is 5% of the mass of silicon slag powder, and the addition amount of binder is silicon slag powder, MgO and Al 2 O 3 1% of mass and;

[0052] In this embodiment, the capsule shell described in S6 has an inner diameter of 10 mm, an inner height of 10 mm, and a thickness of 2 mm. The inner diameter of the capsule cover is 2 mm larger than the outer diameter of the shell, the inner height is consistent with the outer height of the shell, and the thickness is 1 mm.

[0053] In this embodiment, the pre-sintering temperature in S6 is 300° C., the heating rate is 3° C. / min, the temperature is kept at 300° C. for 60 min, and then the temperature is naturally lowered.

[0054] In this embodiment, the sintering temperature in S8 is 1100° C., the temperature is kept for 100 min, and the heating and cooling rate is 5° C. / min.

[0055] The prepared heat storage capsules were continuously subjected to heat absorption and release cycles at a temperature of 500-1000°C. The thermal performance analysis of the core material after different heat absorption and release cycles is as follows:

[0056] Cycle times / times Melting start temperature / ℃ Melting end temperature / ℃ <![CDATA[Phase change heat absorption / J·g -1 <!-- 4 -->]]> 0 789 806 215 50 790 810 208 100 790 810 201

[0057] Example 2

[0058] As described in this embodiment, a method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts has the following specific steps:

[0059] S1, calcining the waste contactor in an argon atmosphere to remove organic matter therein;

[0060] S2, mixing the waste contact body processed in S1 with a certain proportion of pure iron powder and pure copper powder;

[0061] S3, alloying the mixed material in S2 using a high energy ball mill;

[0062] S4, grinding the industrial silicon slag and sieving to obtain silicon slag powder with a target particle size;

[0063] S5, the silicon slag powder obtained from S4 and a certain amount of MgO and Al 2 O 3 The powder, soluble starch or sodium carboxymethyl cellulose binder are mixed evenly, and then a certain amount of water is added to the mixture by spraying and stirring continuously to slurry the powder;

[0064] S6, injecting the slurry obtained in S5 into a cylindrical mold, pressing to obtain a matching capsule body and capsule cover, and pre-sintering after demoulding;

[0065] S7, encapsulating the alloy powder obtained in S3 into the capsule shell obtained in S6, and filling the gap between the capsule shell and the capsule cover with the slurry in S5;

[0066] S8, subjecting the capsule obtained in S7 to high temperature sintering and sealing treatment.

[0067] In this embodiment, the calcination temperature in S1 is 420° C., and the calcination time is 55 min.

[0068] In this embodiment, the amount of iron powder added in S2 is 1 times the mass of the waste contact body, and the amount of copper powder added is 2 times the mass of the waste contact body;

[0069] In this embodiment, the high-energy ball mill described in S3 is vacuumed, and the ball mill parameters are set to a speed of 400 r / min, forward rotation for 15 min / time, pause for 5 min, reverse rotation for 15 min / time, and a total ball milling time of 17 h;

[0070] In this embodiment, the particle size of the silicon slag powder described in S4 is required to be less than 100 μm;

[0071] In this embodiment, the amount of MgO added in S5 is 2% of the mass of silicon slag powder, and Al 2 O 3 The addition amount is 8% of the mass of silicon slag powder, and the addition amount of binder is silicon slag powder, MgO and Al 2 O 3 2% of the mass sum;

[0072] In this embodiment, the capsule shell described in S6 has an inner diameter of 100 mm, an inner height of 120 mm, and a thickness of 3 mm. The inner diameter of the capsule cover is 3 mm larger than the outer diameter of the shell, the inner height is consistent with the outer height of the shell, and the thickness is 2 mm.

[0073] In this embodiment, the pre-sintering temperature in S6 is 300° C., the heating rate is 3° C. / min, the temperature is kept at 300° C. for 75 min, and then the temperature is naturally lowered.

[0074] In this embodiment, the sintering temperature in S8 is 1200° C., the temperature is kept for 150 min, and the heating and cooling rate is 5° C. / min.

[0075] The prepared heat storage capsules were continuously subjected to heat absorption and release cycles at a temperature of 500-1000°C. The thermal performance analysis of the core material after different heat absorption and release cycles is as follows:

[0076] Cycle times / times Melting start temperature / ℃ Melting end temperature / ℃ <![CDATA[Phase change heat absorption / J·g -1 > 0 792 850 234 50 791 855 211 100 793 855 216

[0077] Example 3

[0078] As described in this embodiment, a method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts has the following specific steps:

[0079] S1, calcining the waste contactor in an argon atmosphere to remove organic matter therein;

[0080] S2, mixing the waste contact body processed in S1 with a certain proportion of pure iron powder and pure copper powder;

[0081] S3, alloying the mixed material in S2 using a high energy ball mill;

[0082] S4, grinding the industrial silicon slag and sieving to obtain silicon slag powder with a target particle size;

[0083] S5, the silicon slag powder obtained from S4 and a certain amount of MgO and Al 2 O 3 The powder, soluble starch or sodium carboxymethyl cellulose binder are mixed evenly, and then a certain amount of water is added to the mixture by spraying and stirring continuously to slurry the powder;

[0084] S6, injecting the slurry obtained in S5 into a cylindrical mold, pressing to obtain a matching capsule body and capsule cover, and pre-sintering after demoulding;

[0085] S7, encapsulating the alloy powder obtained in S3 into the capsule shell obtained in S6, and filling the gap between the capsule shell and the capsule cover with the slurry in S5;

[0086] S8, subjecting the capsule obtained in S7 to high temperature sintering and sealing treatment.

[0087] In this embodiment, the calcination temperature in S1 is 580° C., and the calcination time is 100 min.

[0088] In this embodiment, the amount of iron powder added in S2 is 1.3 times the mass of the waste contact body, and the amount of copper powder added is 3 times the mass of the waste contact body;

[0089] In this embodiment, the high-energy ball mill described in S3 is vacuumized, and the ball mill parameters are set to a speed of 450 r / min, forward rotation for 20 min / time, pause for 5 min, reverse rotation for 20 min / time, and a total ball milling time of 19 h;

[0090] In this embodiment, the particle size of the silicon slag powder described in S4 is required to be less than 100 μm;

[0091] In this embodiment, the amount of MgO added in S5 is 5% of the mass of the silicon slag powder, and the amount of Al 2 O 3 The addition amount is 10% of the mass of silicon slag powder, and the addition amount of binder is silicon slag powder, MgO and Al 2 O 3 3% of mass and;

[0092] In this embodiment, the capsule shell described in S6 has an inner diameter of 300 mm, an inner height of 500 mm, and a thickness of 3 mm. The inner diameter of the capsule cover is 3 mm larger than the outer diameter of the shell, the inner height is consistent with the outer height of the shell, and the thickness is 2 mm.

[0093] In this embodiment, the pre-sintering temperature in S6 is 300° C., the heating rate is 3° C. / min, the temperature is kept at 300° C. for 100 min, and then the temperature is naturally lowered.

[0094] In this embodiment, the sintering temperature in S8 is 1125° C., the temperature is kept for 160 min, and the heating and cooling rate is 5° C. / min.

[0095] The prepared heat storage capsules were continuously subjected to heat absorption and release cycles at a temperature of 500-1000°C. The thermal performance analysis of the core material after different heat absorption and release cycles is as follows:

[0096] Cycle times / times Melting start temperature / ℃ Melting end temperature / ℃ <![CDATA[Phase change heat absorption / J·g -1 > 0 799 845 221 50 801 920 198 100 800 922 199

[0097] Example 4

[0098] As described in this embodiment, a method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts has the following specific steps:

[0099] S1, calcining the waste contactor in an argon atmosphere to remove organic matter therein;

[0100] S2, mixing the waste contact body processed in S1 with a certain proportion of pure iron powder and pure copper powder;

[0101] S3, alloying the mixed material in S2 using a high energy ball mill;

[0102] S4, grinding the industrial silicon slag and sieving to obtain silicon slag powder with a target particle size;

[0103] S5, the silicon slag powder obtained from S4 and a certain amount of MgO and Al 2 O 3 The powder, soluble starch or sodium carboxymethyl cellulose binder are mixed evenly, and then a certain amount of water is added to the mixture by spraying and stirring continuously to slurry the powder;

[0104] S6, injecting the slurry obtained in S5 into a cylindrical mold, pressing to obtain a matching capsule body and capsule cover, and pre-sintering after demoulding;

[0105] S7, encapsulating the alloy powder obtained in S3 into the capsule shell obtained in S6, and filling the gap between the capsule shell and the capsule cover with the slurry in S5;

[0106] S8, subjecting the capsule obtained in S7 to high temperature sintering and sealing treatment.

[0107] In this embodiment, the calcination temperature in S1 is 800° C. and the calcination time is 60 min.

[0108] In this embodiment, the amount of iron powder added in S2 is 1.7 times the mass of the waste contact body, and the amount of copper powder added is 4 times the mass of the waste contact body;

[0109] In this embodiment, the high-energy ball mill described in S3 is vacuumed, and the ball mill parameters are set to a speed of 580 r / min, forward rotation of 25 min / time, pause of 5 min, reverse rotation of 25 min / time, and a total ball milling time of 25 h;

[0110] In this embodiment, the particle size of the silicon slag powder described in S4 is required to be less than 100 μm;

[0111] In this embodiment, the amount of MgO added in S5 is 8% of the mass of silicon slag powder, and Al 2 O 3 The addition amount is 13% of the mass of silicon slag powder, and the addition amount of binder is silicon slag powder, MgO and Al 2 O 3 4% of mass and;

[0112] In this embodiment, the inner diameter of the capsule shell described in S6 is 450 mm, the inner height is 200 mm, and the thickness is 4.5 mm. The inner diameter of the capsule cover is 5 mm larger than the outer diameter of the shell, the inner height is consistent with the outer height of the shell, and the thickness is 4 mm.

[0113] In this embodiment, the pre-sintering temperature in S6 is 300° C., the heating rate is 3° C. / min, the temperature is kept at 300° C. for 120 min, and then the temperature is naturally lowered.

[0114] In this embodiment, the sintering temperature in S8 is 1300° C., the temperature is kept for 150 min, and the heating and cooling rate is 5° C. / min.

[0115] The prepared heat storage capsules were continuously subjected to heat absorption and release cycles at a temperature of 500-1000°C. The thermal performance analysis of the core material after different heat absorption and release cycles is as follows:

[0116] Cycle times / times Melting start temperature / ℃ Melting end temperature / ℃ <![CDATA[Phase change heat absorption / J·g -1 > 0 801 911 267 50 705 900 255 100 801 910 234

[0117] Example 5

[0118] As described in this embodiment, a method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts has the following specific steps:

[0119] S1, calcining the waste contactor in an argon atmosphere to remove organic matter therein;

[0120] S2, mixing the waste contact body processed in S1 with a certain proportion of pure iron powder and pure copper powder;

[0121] S3, alloying the mixed material in S2 using a high energy ball mill;

[0122] S4, grinding the industrial silicon slag and sieving to obtain silicon slag powder with a target particle size;

[0123] S5, the silicon slag powder obtained from S4 and a certain amount of MgO and Al 2 O 3 The powder, soluble starch or sodium carboxymethyl cellulose binder are mixed evenly, and then a certain amount of water is added to the mixture by spraying and stirring continuously to slurry the powder;

[0124] S6, injecting the slurry obtained in S5 into a cylindrical mold, pressing to obtain a matching capsule body and capsule cover, and pre-sintering after demoulding;

[0125] S7, encapsulating the alloy powder obtained in S3 into the capsule shell obtained in S6, and filling the gap between the capsule shell and the capsule cover with the slurry in S5;

[0126] S8, subjecting the capsule obtained in S7 to high temperature sintering and sealing treatment.

[0127] In this embodiment, the calcination temperature in S1 is 900° C. and the calcination time is 300 min.

[0128] In this embodiment, the amount of iron powder added in S2 is twice the mass of the waste contact body, and the amount of copper powder added is five times the mass of the waste contact body;

[0129] In this embodiment, the high-energy ball mill described in S3 is vacuumed, and the ball mill parameters are set to a speed of 600 r / min, forward rotation for 30 min / time, pause for 5 min, reverse rotation for 30 min / time, and a total ball milling time of 30 h;

[0130] In this embodiment, the particle size of the silicon slag powder described in S4 is required to be less than 100 μm;

[0131] In this embodiment, the amount of MgO added in S5 is 10% of the mass of the silicon slag powder. 2 O 3 The addition amount is 20% of the mass of silicon slag powder, and the addition amount of binder is silicon slag powder, MgO and Al 2 O 3 5% of the mass sum;

[0132] In this embodiment, the capsule shell described in S6 has an inner diameter of 500 mm, an inner height of 1000 mm, and a thickness of 5 mm. The inner diameter of the capsule cover is 5 mm larger than the outer diameter of the shell, the inner height is consistent with the outer height of the shell, and the thickness is 5 mm.

[0133] In this embodiment, the pre-sintering temperature in S6 is 300° C., the heating rate is 3° C. / min, the temperature is kept at 300° C. for 150 min, and then the temperature is naturally lowered.

[0134] In this embodiment, the sintering temperature in S8 is 1500° C., the temperature is kept for 200 min, and the heating and cooling rate is 5° C. / min.

[0135] The prepared heat storage capsules were continuously subjected to heat absorption and release cycles at a temperature of 500-1000°C. The thermal performance analysis of the core material after different heat absorption and release cycles is as follows:

[0136] Cycle times / times Melting start temperature / ℃ Melting end temperature / ℃ <![CDATA[Phase change heat absorption / J·g -1 > 0 801 897 251 50 806 884 248 100 799 905 243

[0137] It can be seen from the above Examples 1 to 5 that the technical solution proposed in the present invention for preparing silicon-copper alloy phase change energy storage capsules using waste organosilicon contacts can simultaneously achieve efficient recycling and treatment of hazardous solid wastes and high-value utilization of valuable components. The prepared energy storage capsules have excellent thermal properties and stability and can be widely used in the field of high-temperature energy storage.

[0138] Example 6: Comparative Example 1

[0139] The remaining steps are the same as those in Example 5, except that the ball milling alloying in step S3 is changed to high temperature melting alloying, using a vacuum resistance furnace, a melting temperature of 1500° C., and a heat preservation time of 120 min. The obtained alloy ingot is powdered and packaged according to the steps in Example 5.

[0140] The prepared heat storage capsules were continuously subjected to heat absorption and release cycles at a temperature of 500-1000°C. The thermal performance analysis of the core material after different heat absorption and release cycles is as follows:

[0141] Cycle times / times Melting start temperature / ℃ Melting end temperature / ℃ <![CDATA[Phase change heat absorption / J·g -1 > 0 801 885 121 50 805 884 117 100 810 910 98

[0142] The heat storage capacity of the heat storage capsule prepared in this comparative example is significantly lower than that of Example 5 under the same number of cycles. The reason is that during the high-temperature smelting and alloying process, the significant density difference of the silicon-copper melt leads to uneven melt composition. After the alloy ingot solidifies, a large amount of silicon exists in the form of elemental silicon and does not form an alloy phase. Since the melting point of elemental silicon is relatively high, its contribution to the heat storage of the capsule is limited. Therefore, ball milling alloying can not only reduce energy consumption, but also provide effective guarantee for homogenizing the alloy composition and improving the heat storage capacity.

[0143] Example 7: Comparative Example 2

[0144] Steps S1-S3 are the same as those in Example 1, but the prepared alloy powder is not encapsulated in a shell, but is microencapsulated. The alloy powder is calcined in an air atmosphere to oxidize its surface to achieve the purpose of self-encapsulation. The calcination temperature is 1000°C and the temperature is kept for 120 min.

[0145] The prepared heat storage microcapsules were continuously subjected to heat absorption and release cycles at a temperature of 500-1000°C. The thermal performance analysis after different heat absorption and release cycles is as follows:

[0146] Cycle times / times Melting start temperature / ℃ Melting end temperature / ℃ <![CDATA[Phase change heat absorption / J·g -1 > 0 811 895 201 50 791 892 106 100 805 911 73

[0147] By comparison with Example 1, the heat absorption before the cycle test is not much different, only slightly reduced. This is because the surface oxide does not undergo phase change heat absorption. However, after the cycle test, it is found that the phase change heat absorption decreases sharply with the increase in the number of cycles. This is because the oxide film generated during the self-oxidation encapsulation process is difficult to prevent the continuous oxidation of the alloy. Therefore, using a stable shell to encapsulate a large-size phase change heat storage capsule is an effective means to improve the thermal properties of the capsule and maintain stability.

[0148] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts, characterized in that: The following steps are involved: S1, calcining the waste organosilicon contact body in an argon atmosphere to remove organic matter therein; S2, mixing the waste silicone contact body treated in S1 with a certain proportion of pure iron powder and pure copper powder; S3, alloying the mixed material in S2 using a high energy ball mill; S4, grinding the industrial silicon slag and sieving to obtain silicon slag powder with a target particle size; S5, uniformly mix the silicon slag powder obtained in S4 with a certain amount of MgO and Al2O3 powder and sodium carboxymethyl cellulose binder, then add a certain amount of water to the mixture by spraying and continuously stir to slurry the powder; S6, injecting the slurry obtained in S5 into a cylindrical mold, pressing to obtain a matching capsule body and capsule cover, and pre-sintering after demoulding; S7, encapsulating the alloy powder obtained in S3 into the capsule shell obtained in S6, and filling the gap between the capsule shell and the capsule cover with the slurry in S5; S8, performing high temperature sintering and sealing treatment on the capsule obtained in S7.

2. The method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts as claimed in claim 1, characterized in that: In the step S1, the calcination temperature is 300-900° C., and the calcination time is 30-300 min.

3. The method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts as claimed in claim 1, characterized in that: The amount of iron powder added in S2 is 0.5 to 2 times the mass of the waste contact body, and the amount of copper powder added is 1 to 5 times the mass of the waste contact body.

4. The method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts as claimed in claim 1, characterized in that: The high-energy ball mill in S3 is subjected to vacuum treatment, and the parameters of the ball mill are set as follows: the rotation speed is 350-600 r / min, the forward rotation is 10-30 min / time, the pause is 5 min, the reverse rotation is 10-30 min / time, and the total ball milling time is 15-30 h.

5. The method for preparing an iron-silicon-copper alloy phase change energy storage capsule using waste organic silicon contacts as claimed in claim 1, characterized in that: The particle size of the silicon slag powder in the S4 is required to be less than 100 μm.

6. The method for preparing an iron-silicon-copper alloy phase-change energy storage capsule using waste organic silicon contacts as claimed in claim 1, characterized in that: The added amount of MgO in the S5 is 1-10% of the mass of the silicon slag powder, the added amount of Al2O3 is 5-20% of the mass of the silicon slag powder, and the added amount of the binder is 1-5% of the total mass of the silicon slag powder, MgO and Al2O3.

7. The method for preparing an iron-silicon-copper alloy phase-change energy storage capsule using waste organic silicon contacts as claimed in claim 1, characterized in that: The capsule shell in S6 has an inner diameter of 10 to 500 mm, an inner height of 10 to 1000 mm, and a thickness of 2 to 5 mm. The inner diameter of the capsule cover is 2 to 5 mm larger than the outer diameter of the shell, the inner height is consistent with the outer height of the shell, and the thickness is 1 to 5 mm. The pre-sintering temperature in S6 is 300° C., the heating rate is 3° C. / min, the temperature is kept at 300° C. for 60 to 150 minutes, and then the temperature is naturally lowered.

8. The method for preparing an iron-silicon-copper alloy phase-change energy storage capsule using waste organic silicon contacts as claimed in claim 1, characterized in that: The sintering temperature in S8 is 1100-1500° C., the temperature is kept for 100-200 min, and the heating and cooling rate is 5° C. / min.

Citation Information

Cited By

  • Method for purifying silicon from organic silicon synthesis waste contact and application in preparation of silicon-based alloy

    CN120887425A

  • Method for purifying silicon from spent catalyst of organic silicon synthesis and use for preparing silicon-based alloys

    CN120887425B

  • Method for preparing silicon-copper alloy by using organic silicon synthesis waste contact body

    CN121428613A